Muscle hypertrophy and neuroplasticity in the small bowel in short bowel syndrome - Khasanov, Rasul; Svoboda, Daniel; Tapia-Laliena, María Angeles; Kohl, Martina; Maas-Omlor, Silke; Hagl, Cornelia Irene; Wessel, Lucas; Schäfer, Karl-Herbert (Histochemistry and cell biology, 2023)
Short bowel syndrome (SBS) is a severe, life-threatening condition and one of the leading causes of intestinal failure in children. Here we were interested in changes in muscle layers and especially in the myenteric plexus of the enteric nervous system (ENS) of the small bowel in the context of intestinal adaptation. Twelve rats underwent a massive resection of the small intestine to induce SBS. Sham laparotomy without small bowel transection was performed in 10 rats. Two weeks after surgery, the remaining jejunum and ileum were harvested and studied. Samples of human small bowel were obtained from patients who underwent resection of small bowel segments due to a medical indication. Morphological changes in the muscle layers and the expression of nestin, a marker for neuronal plasticity, were studied. Following SBS, muscle tissue increases significantly in both parts of the small bowel, i.e., jejunum and ileum. The leading pathophysiological mechanism of these changes is hypertrophy. Additionally, we observed an increased nestin expression in the myenteric plexus in the remaining bowel with SBS. Our human data also showed that in patients with SBS, the proportion of stem cells in the myenteric plexus had risen by more than twofold. Our findings suggest that the ENS is tightly connected to changes in intestinal muscle layers and is critically involved in the process of intestinal adaptation to SBS.
Online veröffentlicht: 3. Juli 2023
Gesehen am 19.09.2024